The Influence Of Innovation And Competency On Employee Performance With Competitive Advantage As An Intevening Variable: Study Of Coffee Shop Employees In Limpung District - Ety Puspitaningtyas; Sutrisno Sutrisno ; Bayu Kurniawan (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The Effect of Innovation and Competence on Employee Performance with Competitive Advantage as an Intervening Variable (Study of Coffee Shop Employees in Limpung District)" This research aims to measure the Effect of Innovation and Competency on Employee Performance with Competitive Advantage as an Intervening Variable (Study of Coffee Shop Employees in the District dizzy). This research is a quantitative type of research, namely using a research instrument in the form of a questionnaire which has been prepared into several statements and measured using a 1-5 Likert scale. The population used in this research was coffee shop employees in Limpung sub-district. The sampling technique uses the Cochran formula. The results of this study state that the variables used have a significant influence on coffee shop employees in Limpung sub-district. The research results show that there is a significant influence between variables.